The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/jes-12-2019-0571
|View full text |Cite
|
Sign up to set email alerts
|

Does terrorism hamper FDI inflows? A pre and post 9/11 analysis

Abstract: PurposeThis research intends to determine the role of terrorism in defying foreign direct investment (FDI) in top terror effected economies.Design/methodology/approachPanel data on FDI and terrorism from top terror effected economies spanning from 1987 to 2018 were used and the relationship for whole sample was investigated. Later the sample period was divided into pre (1987–2001) and post 9/11 (2002–2018) subsample and same relationship was tested to investigate the normalization of terror effect on FDI. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…The empirical analysis presents us with a number of statistical difficulties. First, there is the potential endogeneity of terrorism and FDI (Arif, Rawat, and Khan 2020; Bandyopadhyay, Sandler, and Younas 2014). Second, our theory is predicated on FDI increasing economic outcomes, which requires us to show a mediating relationship.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical analysis presents us with a number of statistical difficulties. First, there is the potential endogeneity of terrorism and FDI (Arif, Rawat, and Khan 2020; Bandyopadhyay, Sandler, and Younas 2014). Second, our theory is predicated on FDI increasing economic outcomes, which requires us to show a mediating relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, countries that engage in successful counter-terrorism efforts, and see a reduction in terror, are often rewarded with increased FDI (Bandyopadhyay, Sandler, and Younas 2014). Such concerns are particularly relevant to the most terror-effected economies, as they have primarily been shut out of the FDI marketplace (Arif, Rawat, and Khan 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, research has found that both business and non-business targeted terrorist attacks reduce foreign investment (Dimitrova et al, 2022), even more so than natural disasters, and specifically in developing nations (Bandyopadhyay et al, 2014). Despite the theoretical arguments consistently positing that terrorism is perceived negatively by MNEs, some scholars have found that terrorist attacks do not have a direct and significant negative effect on MNEs' investments, at least in more recent years and in certain industries (Arif et al, 2021;Liu and Li, 2020;Skovoroda et al, 2019).…”
Section: Violent Political Riskmentioning
confidence: 99%
“…Hyeong Joon Kim https://orcid.org/0000-0001-9179-4974 NOTES 1 For evidence on the impact of terrorism on macroeconomic outcomes at the industry or national levels, see, for example, Arif et al (2020), Baker (2014), Chen et al (2021), Eckstein and Tsiddon (2004), Tingbani et al (2019), andWaxman (2011). 2 The differences between our study and Lins et al (2017) are the measure of social capital and traumatic events.…”
Section: Orcidmentioning
confidence: 99%
“… For evidence on the impact of terrorism on macroeconomic outcomes at the industry or national levels, see, for example, Arif et al (2020), Baker (2014), Chen et al (2021), Eckstein and Tsiddon (2004), Tingbani et al (2019), and Waxman (2011). …”
mentioning
confidence: 99%